(Im)possibility of practice: Satirical objectification and essaying projects. (1st December 2015) - Robbins, Felix
This article develops the notion of 'tipping points' with respect to the gaps and slippages in my architectural practice, and the consequences when considered in terms of projecting for architecture as opposed to the production of architecture. It adopts as a 'starting point' the insecurities of the discipline and the predominance of 'models of' architecture conceived as a 'problem-solving' exercise. It adopts a sceptical reflection on the premise of the discipline, and the value of its product – suggesting that the perpetuation of positions to justify a product merely exacerbate the impossibility of practice. The 'objectification' of the discipline is contrasted with the potential dynamics of 'projection' – exploring a shift in emphasis towards 'projecting' as a means to enable complex and dynamic 'models for' architecture. This shift is investigated through my ongoing design research that moves within the contradictions, translations and uncertainties of historical and projective slippages of 'reconstructions' and 'parts' of houses. My projects speculate on the contingent opportunities of inhabiting an open sequence of a 'problematic situation', rather than the singular limitations of a 'solution' to a 'problem'. My research moves towards considering the liberating potential of acknowledging that contradiction is the architectural project, rather than perpetually conceiving of contradiction as an obstacle to be repositioned or removed by the construction of an architectural product. This shift in emphasis is considered as an open sequence of 'tipping points' that continue to evolve within the contradictions of practice as models for projecting architecture, rather than a singular 'tipping point' that simply reconstructs the same model of architectural product in different terms. The tipping point in my research is ultimately an acknowledgement of the (im)possibility of practice – the inherent contradiction in projecting an architectural project that by necessity is initiated by the belief in a transformative and ameliorative quality to 'projecting', but also necessarily without the capacity to articulate what that quality is.